Unveiling water stress responses in rice: Identifying traits for enhanced water-use efficiency - Aziz, Irum; Aslam, Zahid; Kamran, Atif; Bashir, Muhammad Amjad; Ali, Mubashir; Hussain, Zahid (Journal of Pure and Applied Agriculture, 2024)
Rice (Oryza sativa L.) is a primary source of nutrition for more than half of the world's population. Rice in the reproductive stages is highly susceptible to water stress, and deficit irrigation leads to a significant decrease in the grain yield. Under such conditions, it is imperative for plant breeders to explore the genetic potential of rice for better yield and quality under limiting watering conditions. Four rice varieties, viz. Super-Basmati (V1), Super Kinat (V2), V-385 (V3) and V-386 (V4) are sown under split-plot design in field conditions. For this, we evaluated the four rice varieties for stage-specific watering thresholds under two distinct water conditions, including normal water conditions (T1) and water deficit conditions (T2), throughout the growth period. The nursery was transplanted in the field after 30-40 days after sowing. The field capacity was measured by estimating the soil water content at 50% and was maintained throughout the growing season. After the harvest, data was recorded for the following traits i.e., plant height (PH), Number of fertile tillers per plant (NFT), Number of fertile tillers per plant (NTP), number of seeds per spike (SPS), days to maturity (DM), number of grains per plant (GPP), 1000 seed weight (TSW), seed length (SL), and seed weight (SW). ANOVA results represent that all these traits are significant except seed length (SL). All four varieties show different responses under normal and drought conditions. Under normal conditions, V4 had significantly lower seed weight than other genotypes, whereas, under water stress conditions, V3 and V4 outperformed V1 and V2 with significantly higher seed weight. Notably V-386, adapt to water stress with increased plant height and improved seed production per spike. However, this resilience comes at a cost, as V-386 exhibits delayed maturity under drought conditions compared to normal circumstances. The association among all morphological traits was studied using Pearson correlation analysis. The results of the correlation study under water deficit conditions showed a completely different trend as compared to normal water application. Principal component analysis was performed to visualize the relationships among the traits among all four varieties. This research suggests that the recorded traits can serve as a selection tool for predicting water-use-efficient genotypes in rice.